Genotyping 1000 yeast strains by next-generation sequencing. - Wilkening, Stefan.; Tekkedil, Manu M.; Lin, Gen.; Fritsch, Emilie S.; Wei, Wu.; Gagneur, Julien.; Lazinski, David W.; Camilli, Andrew.; Steinmetz, Lars M. (2016)
Background: The throughput of next-generation sequencing machines has increased dramatically over the last few years; yet the cost and time for library preparation have not changed proportionally, thus representing the main bottleneck for sequencing large numbers of samples. Here we present an economical, high-throughput library preparation method for the Illumina platform, comprising a 96-well based method for DNA isolation for yeast cells, a low-cost DNA shearing alternative, and adapter ligation using heat inactivation of enzymes instead of bead cleanups.; Keywords: Next-generation sequencing, High throughput, DNA isolation, Yeast, DNA fragmentation, Heat inactivation, Recombination, Aneuploidy.; Springer Open.